2000
DOI: 10.1302/0301-620x.82b1.0820116
|View full text |Cite
|
Sign up to set email alerts
|

Graded compression stockings in elective orthopaedic surgery

Abstract: We recruited 89 patients who had hip or knee replacements to assess the performance of below-knee graded compression stockings. The pressure gradients generated by the stockings were measured and all patients had venography of the ipsilateral leg.We found that 98% of stockings failed to produce the 'ideal' pressure gradient (± 20%) of 18, 14 and 8 mmHg from the ankle to the knee, while 54% produced a 'reversed gradient' on at least one occasion during the course of the study. The overall rate of deep-venous th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On the one hand, insufficient interface pressures could result in inadequate treatment of chronic venous insufficiency and consequent delayed improvement or lack of improvement in symptoms of chronic venous insufficiency such as edema, eczema, hyperpigmentation, and ulceration. On the other hand, excessive ankle interface pressures could cause skin necrosis and thrombosis 7–9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, insufficient interface pressures could result in inadequate treatment of chronic venous insufficiency and consequent delayed improvement or lack of improvement in symptoms of chronic venous insufficiency such as edema, eczema, hyperpigmentation, and ulceration. On the other hand, excessive ankle interface pressures could cause skin necrosis and thrombosis 7–9 …”
Section: Discussionmentioning
confidence: 99%
“…As a result of a poorly fitting compression bandage or stocking, nerve lesions, blistering, erosions, and even ulceration can prolong or complicate an existing venous condition 7,8 . Band‐like constrictions due to compression therapy can increase the risk of deep vein thrombosis 9 …”
Section: Ankle Interface Pressures Of Compression Stockings Accordimentioning
confidence: 99%
“…However, Best et al (2000) found that 98% of stockings failed to produce the 'ideal' pressure gradient of 18, 14 and 8 mmHg from the ankle to the knee, while 54% produced a 'reversed gradient' on at least one occasion. …”
Section: Graded Compression Stockingsmentioning
confidence: 98%